Novel Genomic and Evolutionary Perspective of Cyanobacterial tRNAs - Mohanta, Tapan K.; Syed, Asad S.; Ameen, Fuad; Bae, Hanhong (Frontiers in Genetics, 2017)
Transfer RNA (tRNA) plays a central role in protein synthesis and acts as an adaptor molecule between an mRNA and an amino acid. A tRNA has an L-shaped clover leaf-like structure and contains an acceptor arm, D-arm, D-loop, anti-codon arm, anti-codon loop, variable loop, Ψ-arm and Ψ-loop. All of these arms and loops are important in protein translation. Here, we aimed to delineate the genomic architecture of these arms and loops in cyanobacterial tRNA. Studies from tRNA sequences from 61 cyanobacterial species showed that, except for few tRNAs (tRNAAsn, tRNALeu, tRNAGln and tRNAMet), all contained a G nucleotide at the 1st position in the acceptor arm. tRNALeu and tRNAMet did not contain any conserved nucleotides at the 1st position whereas tRNAAsn and tRNAGln contained a conserved U1 nucleotide. In several tRNA families, the variable region also contained conserved nucleotides. Except for tRNAMet and tRNAGlu, all other tRNAs contained a conserved A nucleotide at the 1st position in the D-loop. The Ψ-loop contained a conserved U1-U2-C3-x-A5-x-U7 sequence, except for tRNAGly, tRNAAla, tRNAVal, tRNAPhe, tRNAThr, and tRNAGln in which the U7 nucleotide was not conserved. However, in tRNAAsp, the U7 nucleotide was substituted with a C7 nucleotide. Additionally, tRNAArg, tRNAGly and tRNALys of cyanobacteria contained a group I intron within the anti-codon loop region. Maximum composite likelihood study on the transition/transversion of cyanobacterial tRNA revealed that the rate of transition was higher than the rate of transversion. An evolutionary tree was constructed to understand the evolution of cyanobacterial tRNA and analyses revealed that cyanobacterial tRNA may have evolved polyphyletically with high rate of gene loss.